ANALYSIS OF DIFFERENCES DEGREE OF SEVERITY AND QUALITY OF LIFE OF BPH DIABETES WITH BPH NON-DIABETES PATIENTS - Kurnia Putra, Prayoga Triyadi; Wahyudi, Septa Surya; Novi M, Ancah Caesarina (Indonesian Urological Association, 2019)
Objective: Benign Prostatic Hyperplasia (BPH) is a benign tumor located in prostate caused by prostate cell that will continuously grows which covalent with the aging process and the dihidrotestosteron level (DHT) increase. Prostate Hyperplasia can stop the urethra pars prostatics and causesa clogging in the urine’s flow excretes from bladder. Lower Urinary Tract Symptomps (LUTS) is a bladder muscle compensation mechanism to excrete urine. Diabetes Mellitus (DM) is one of the risk factors of BPH. This research aimed to find the differences on the degree of severity and quality of life BPH DM with BPH non-DM. Material & Methods: This research was observational analytic with cross sectional design which done to 32 subjects that consist of 16 BPH-DM subjects and 16 BPH non-DM in Bina Sehat Hospital Jember, Paru Hospital Jember, and Bhayangkara Hospital Bondowoso which meet to the inclusion and exclusion criteria. Data acquired from lead interview result using International Prostate Symptoms Score (IPSS) questionnaire to evaluate the degree of severity and World Health Organization Quality of Life (WHOQOL-BREF) questionnaire to evaluate the quality of life. The data processing using Mann Whitney’s comparative test. Results: IPSS and physic domain, psychology and social had p value in a row 0.001; 0.000; 0.001; and 0.001. Conclusion: It showed that there was a meaningful difference between BPH DM with BPH non-DM. Environment domain had p value of 0.373. It showed the non-meaningful difference between BPH DM with BPH non-DM.